A Straightforward Route to Homoallyl‐Homocrotylamines Promoted by a Titanium Complex. Issue 4 (14th December 2012) - Toulot, Stéphanie; Bonnin, Quentin; Comte, Virginie; Adriaenssens, Louis; Richard, Philippe; Le Gendre, Pierre
Abstract: π‐Allyltitanium complexes, generated in situ from 1, 3‐dienes and [Cp2 TiH], react with benzotriazole derivatives to give homoallylic amines in good yields. Under similar conditions, triple cascade reactions (allyltitanation followed by cationic 2‐aza‐Cope rearrangement followed by a second allyltitanation) occur from bis(benzotriazolyl) compounds affording a straightforward route to homoallyl‐( E )‐homocrotylamines. A theoretical study provides further insight into the factors that govern the selectivity of this sequence of reactions. Abstract : The titanium‐promoted reductive coupling of 1, 3‐dienes with bis(benzotriazolyl) compounds as substrates led selectively to homoallyl‐homocrotylamines through a triple cascade reaction (allyltitanation – cationic 2‐aza‐Cope rearrangement – allyltitanation).